Radionuclide Renogram Findings in Different Kidney Diseases Referred to Institute of Nuclear Medicine and Allied Science (INMAS) (Bangladesh Medical Journal, 2021)
Renal function evaluation with the use of radio nuclide scanning is a very helpful technique. Renogram is a routine procedure in the Institute of Nuclear Medicine and Allied Sciences (INMAS), Sylhet. This is a tertiary referral hospital to north east part of the country. The aim of this study was to analyze the renal disease pattern and outcome of diuretic renogram of different types of renal diseases. This retrospective study was conducted among 223 patients who underwent 99mTc-DTPA renogram from February to October 2018 in INMAS, Sylhet. Mean age of the patients was 30.04 ± 18.52 year with age range 1 to 80 years, male to female ratio 1.5:1. USG. Clinical information and other adjuvant findings along with the ultrasound findings were collected to categorize the study subject. Most common indication for the renogram was hydronephrosis (HDN) 80.27%, followed by smaller kidney 7.17%, renal parenchymal disease 3.14%, nephrolithiasis 3.14% and others (renal cysts and renal artery stenosis). The mean and standard deviation of serum creatinine was 0.9 ± 0.51, range from 0.30 to 4.50. Among the 179 HDN patients, mild, moderate and severe cases were 37 (20.7%), 44 (24.6%) and 81 (45.3%) respectively. Most common site of involvement was left kidney (n=90, 41.3%), followed by both kidneys (n=67, 30.7%). Overall renographic findings showed obstructive disease in 144 (66.05%) patients and non- obstructive disease in 74 (33.94%) patients. It concluded that isotope renogram is very important in the evaluation of renal function especially differentiate between obstructive from non-obstructive pathology.Bangladesh Med J. 2021 January; 50(1) : 10-14